In silico Docking Studies of Fingolimod and S1P1 Agonists - Marciniak, Alexander; Camp, Sara M.; Garcia, Joe G. N.; Polt, Robin (Frontiers in Pharmacology, 2020)
The Sphingosine-1-Phosphate receptor 1 (S1P1), originally the Endothelial Differentiation Gene 1 receptor (EDG-1), is one of five G Protein–Coupled Receptors (GPCRs) S1P1–5 that bind to and are activated by Sphingosine-1-Phosphate (S1P). The lipid S1P is an intermediate in sphingolipid homeostasis, and S1P1 is a major medical target for immune system modulation; agonism of the receptor produces a myriad of biological responses, including endothelial cell barrier integrity, chemotaxis, lymphocyte trafficking/targeting, angiogenesis, as well as regulation of the cardiovascular system. Use of in silico docking simulations on the crystal structure of S1P1 allows for pinpointing the residues within the receptor’s active site that actively contribute to the binding of S1P, and point to how these specific interactions can be exploited to design more effective synthetic analogues to specifically target S1P1 in the presence of the closely related receptors S1P2, S1P3, S1P4 and S1P5. We examined the binding properties of the endogenous substrate as well as a selection of synthetic sphingosine-derived S1P1 modulators of S1P1 with in silico docking simulations using the software package Molecular Operating Environment® (MOE®). The modeling studies reveal the relevance of phosphorylation, i.e. the presence of a phosphate or phosphonate moiety within the substrate for successful binding to occur, and indicate which residues are responsible for S1P1 binding of the most prominent S1PR modulators, including fingolimod and its structural relatives. Furthermore, trends in steric preferences as for the binding of enantiomers to S1P1 could be observed, facilitating future design of receptor-specific substrates to precisely target the active site of S1P1.